Implementation of the Right to Privacy in the Lithuanian Law on Patients’ Rights - Kutkauskienė, Jelena (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
The individual’s right to a private life is considered to be a vital part of legal systems in democratic countries. The principle of privacy is consistently established in international documents regulating civil and political rights, such as the 1948 Universal Declaration of Human Rights (Art 12), 1950 European Convention on Human Rights (Art 8 Para 1) and other special documents governing patients’ rights. In Lithuanian constitutional doctrine it is acknowledged that the individual’s privacy is inviolable. Furthermore, sources of health law define the scope of patients’ confidential information as well as the conditions for recording, storing and disclosing such information.The article seeks to explore the scope of patients’ confidential information, its legal protection and limitation of patients’ right to privacy according to the Lithuanian Law on the Rights of Patients and Compensation for the Damage to Their Health.Analysis reveals that the legislator has established a non-exhaustive list of personal information related to health, and that there are uncertainties regarding both the scope of collection of personal information and the scope of protection of personal information. A wide variety of obligations are set forth with regard to health care services providers (including some practically unfulfillable obligations) with complex conditions for personal information disclosure to third parties serving as an example of exaggerated legal protection. Furthermore, presumptions are made that regulation of a doctor’s duty to warn patients would solve ethical dilemmas associated with discloser of a patient’s confidential information without consent and would grant legal certainty with regard to a doctor’s obligation to protect third parties from damage that can be avoided.
Keywords: prawo do życia prywatnego; prawa jednostki; Litwa